2010
DOI: 10.1016/j.crvi.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of grazing on the species richness of plant communities in Mediterranean temporary pools (western Morocco)

Abstract: The impact of grazing on the vegetation of Moroccan temporary pools has been studied at 2 scales: regional (inter-pools) and local (intra-pools). Half of the 16 forest pools studied is located in a reserve and ungrazed. The other half, located within public forest, is grazed. Vegetation releve´s coupled to water-depths measurements were carried out in each pool. The results showed a significant effect of grazing on both scales of analysis. This effect was found in the species composition of the vegetation, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
5
25
2
3
Order By: Relevance
“…Colonizing species (macroinvertebrates) were unaffected by livestock treatments, but richness and density were higher in agricultural ponds than forest ponds. This contrasts with other studies that have shown either a positive (Davis & Bidwell, 2008;Marty, 2005) or a negative (Bouahim et al, 2010;Davidson et al, 2017;Epele & Miserendino, 2015;Foote & Hornung, 2005) effect of grazing on the colonisation of ponds by macroinvertebrates. As these taxa arrived in mesocosms from the surrounding landscape, habitat choice becomes an important factor in their distribution and abundance (e.g.…”
Section: Aquatic Communitycontrasting
confidence: 99%
See 4 more Smart Citations
“…Colonizing species (macroinvertebrates) were unaffected by livestock treatments, but richness and density were higher in agricultural ponds than forest ponds. This contrasts with other studies that have shown either a positive (Davis & Bidwell, 2008;Marty, 2005) or a negative (Bouahim et al, 2010;Davidson et al, 2017;Epele & Miserendino, 2015;Foote & Hornung, 2005) effect of grazing on the colonisation of ponds by macroinvertebrates. As these taxa arrived in mesocosms from the surrounding landscape, habitat choice becomes an important factor in their distribution and abundance (e.g.…”
Section: Aquatic Communitycontrasting
confidence: 99%
“…Trampling can be beneficial for some plant species, by the formation of microhabitats in the sediment (Barry, ). This may have a positive effect on smaller fragile species with poor competitive abilities, as found with the rare pillwort Pilularia minuta (Bouahim et al., ). Lastly, it must be noted that R. baudotii , a deeply rooted tolerant species in Triops ‐disturbed mesocosms (Croel & Kneitel, ; Waterkeyn et al., ) flourished in undisturbed conditions in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations